What is the relationship between evaluation and performance of Church of Uganda Projects in Namirembe Diocese? - Katimbo, Duncan; Okoche, John Micheal Maxel (International Journal of Culture and Religious Studies, 2022)
Purpose: Evaluation as a good management practice and an integral function of the project life cycle improves project performance (Shapiro, 2007; Nyonje et al, 2012; Shelber, 2014). The Church of Uganda planned various evaluations to determine the performance of the strategic plan 2025. This paper examined the relationship between evaluation and performance of Church of Uganda Projects in Namirembe Diocese. Methodology: A Cross sectional survey design was used on a study population of 117 respondents. 87 respondents filled the Survey questionnaires whose responses were analysed by using correlational and regression analysis by using PSPP software Version 1.2.0-g0fb4db. Key Informant interviews and an FGD were carried out and responses were analysed using content analysis and results presented as text. The empirical results were presented in frequencies, percentages and summarized into tables. Findings: Descriptive findings highlighted that evaluation to some extent improves project performance (mean 3.1), This was further supported by the qualitative findings. However, inferential statistics revealed that evaluation had a non-significant positive relationship with Project performance (Î²=0.17, p= 0.188>0.05). Unique contribution to theory, practice and policy: In conclusion, this paper established that evaluation to some extent influences project performance. The weaknesses included; having impromptu evaluations of what has not been monitored, lack of evaluation skills and knowledge, lack of commitment from staff, lack of allegiance to the Diocese and only local parish focus, lack of having set Key performance indicators (KPIs) and baseline information. Therefore, to improve upon the performance of Church of Uganda projects, it is important to strengthen the evaluation mechanisms; baseline evaluation, mid-term evaluation and end-term evaluation. The non-existent evaluation framework will be developed with informed decisions from the study.